2016
DOI: 10.1002/agr.21458
|View full text |Cite
|
Sign up to set email alerts
|

Firm Size and Financial Performance: Intermediate Effects of Indebtedness

Abstract: This paper offers a new perspective for the agricultural economics literature on the relationship between firm size and financial performance. We contribute to the literature by exploring the role of indebtedness in this relationship. Using archival data collected from 83 companies belonging to livestock industries, the empirical findings confirm the hypothesis that indebtedness leverages the effect of size on financial performance. That is to say, indebtedness can enhance the realization of the potential bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The ratio of total debt to total assets (LEVERAGE) has a strong negative impact on both ROA and ROS (Table 4). Additional monitoring provided by the debt issuers might be a substitute for poor corporate governance, which in turn might positively impact firm performance (Lopez-Valeiras et al, 2016). On the other hand, González (2013) suggests that if the cost of debt is too high, it might outweigh the positive effects of any additional monitoring by debt issuers, therefore having an overall negative impact on performance.…”
Section: Resultsmentioning
confidence: 99%
“…The ratio of total debt to total assets (LEVERAGE) has a strong negative impact on both ROA and ROS (Table 4). Additional monitoring provided by the debt issuers might be a substitute for poor corporate governance, which in turn might positively impact firm performance (Lopez-Valeiras et al, 2016). On the other hand, González (2013) suggests that if the cost of debt is too high, it might outweigh the positive effects of any additional monitoring by debt issuers, therefore having an overall negative impact on performance.…”
Section: Resultsmentioning
confidence: 99%
“…There is a positive significant relationship between size and profitability (Liargovas and Skandalis, 2008;Akhavein et al, 1997;Smirlock, 1985). More recently, Lopez-Valeiras et al (2016) revealed that the relationship between size and financial performance is negatively mediated by indebtedness.…”
Section: Firm Characteristicsmentioning
confidence: 99%
“…Therefore, firm size influences the ability to raise external funds, thus affecting the companies' debt ratio. A more indebted company may have its competitiveness limited by the ability to make decisions, while greater financial capacity allows greater flexibility in adapting to the product and technological changes, leading to a better adaptation to consumer demand [36]. Thus, studies show that large companies can obtain higher levels of return on assets [37][38][39], higher levels of return on equity or invested capital, higher profit margins or higher returns on sales [40].…”
Section: Firm Size and Corporate Financial Performancementioning
confidence: 99%
“…For example, the financial performance measured as ROA shows both positive and negative effects [37,39]. This lack of conclusive evidence indicates that the effect of size on performance can result from variable moderators, such as productivity [36,44], or control variables such as company age [45,46]. Another explanation for divergent results may come from the different methods applied.…”
Section: Firm Size and Corporate Financial Performancementioning
confidence: 99%